Caregivers' Experiences with Caring for a Child Living with HIV/AIDS: A Qualitative Study in Northern Ghana - Gideon Awenabisa Atanuriba; Felix Apiribu; Adwoa Bemah Boamah Mensah; Veronica Millicent Dzomeku; Richard Adongo Afaya; Timothy Gazari; Joseph Kuufaakang Kuunibe; Philemon Adoliwine Amooba (SAGE Publishing, 2021)
With the advent of Anti-Retroviral Therapy, Human Immune Virus, and Acquire Immuno-Deficiency Syndrome is increasingly becoming a chronic disease as life expectancy among People Living With HIV/AIDS has increased. For Children Living With HIV/AIDS the role of the caregivers becomes essential as caregivers' decisions affect CLWH health. However, the experiences of these caregivers are often unnoticed while all interventions are directed at PLWH. This study aimed at exploring the experiences of caregivers of CLWH in some selected hospitals in northern Ghana. This study employed a qualitative descriptive phenomenological approach. Purposive sampling technique was used to recruit 9 participants from 3 public hospitals in the Tamale Metropolis of Ghana. Data was manually analyzed using the approach of Collaizi and the findings were presented in themes and sub-themes. We conducted individual face to face interviews in English and Dagbani from September to November 2019. These interviews were conducted at the convenience of the participants in hospitals and at their homes. They were introduced to the study while awaiting to take antivirals for their CLWH. Five themes emerged: changed family dynamics, discovery of diagnosis, reaction to diagnosis, disclosure, stigma and discrimination, and burden and challenges of care. Caregivers were severely impacted by caring for CLWH and traumatized by changed family dynamics which exposed them to many difficulties. Stigma was widely perpetrated by immediate family members and majority reacted badly to their children HIV-positive status with fear, shame, guilt and even suicidal ideation.